2021
DOI: 10.1103/physrevb.103.l140105
|View full text |Cite|
|
Sign up to set email alerts
|

Structure and composition of C-S-H compounds up to 143 GPa

Abstract: We synthesized two C-S-H compounds from a mixture of carbon and sulfur in hydrogen-C : (H 2 S) 2 H 2 and from sulfur in mixed methane-hydrogen fluids-(CH 4 ) x (H 2 S) (2−x) H 2 at 4 GPa. X-ray synchrotron single-crystal diffraction and Raman spectroscopy have been applied to these samples up to 58 and 143 GPa, respectively. Both samples show a similar Al 2 Cu-type I4/mcm basic symmetry, while the hydrogen subsystem evolves with pressure via variously ordered molecular and extended modifications. The methane-b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
22
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 37 publications
(97 reference statements)
4
22
2
Order By: Relevance
“…The overall general volume trends for all of the C-S-H crystals measured are equal or lower than that of our own measurements on pure H 2 S+H 2 , which in turn is noticeably lower than that reported for C-S-H prepared from from mixtures of molecular H 2 S+CH 4 +H 2 gases. [26] At low pressures (18 GPa), SC-XRD measurements confirm phase I [1] as the Al 2 Cu-type structure (I4/mcm) previously identified in molecular mixtures of CH 4 and H 2 , [18] and in H 2 S and H 2 . [19,26] The I4/mcm phase is inferred between 4 to 9 GPa as no observed change occurred in Raman spectroscopy.…”
supporting
confidence: 63%
See 3 more Smart Citations
“…The overall general volume trends for all of the C-S-H crystals measured are equal or lower than that of our own measurements on pure H 2 S+H 2 , which in turn is noticeably lower than that reported for C-S-H prepared from from mixtures of molecular H 2 S+CH 4 +H 2 gases. [26] At low pressures (18 GPa), SC-XRD measurements confirm phase I [1] as the Al 2 Cu-type structure (I4/mcm) previously identified in molecular mixtures of CH 4 and H 2 , [18] and in H 2 S and H 2 . [19,26] The I4/mcm phase is inferred between 4 to 9 GPa as no observed change occurred in Raman spectroscopy.…”
supporting
confidence: 63%
“…[26] At low pressures (18 GPa), SC-XRD measurements confirm phase I [1] as the Al 2 Cu-type structure (I4/mcm) previously identified in molecular mixtures of CH 4 and H 2 , [18] and in H 2 S and H 2 . [19,26] The I4/mcm phase is inferred between 4 to 9 GPa as no observed change occurred in Raman spectroscopy. Due to insufficient C concentration or unique crystallographic placements, SC-XRD measurements are unable to resolve between C and S on the 8h Wyckoff positions, thus Figure 3a displays only H 2 S units on the 8h sites.…”
supporting
confidence: 63%
See 2 more Smart Citations
“…those for 020o and 201o are estimated from the observed spread in the data. 31 Figure 5 shows the P-V relations obtained from diffraction data as a function of pressure from 124 to 178 GPa. We also compare the measured volumes reported for the C-S-H material by Bykova et al 31 and those reported for S-H phases.…”
Section: Figure 3 Pressure Dependence Of D-spacings Determined From I...mentioning
confidence: 99%